O-linked β- N-acetylglucosamine ( O-GlcNAc): Extensive crosstalk with phosphorylation to regulate signaling and transcription in response to nutrients and stress - Butkinaree, Chutikarn; Park, Kyoungsook; Hart, Gerald W. (Biochimica et biophysica acta, 2010)
Since its discovery in the early 1980s, O-linked-β- N-acetylglucosamine (O-GlcNAc), a single sugar modification on the hydroxyl group of serine or threonine residues, has changed our views of protein glycosylation. While other forms of protein glycosylation modify proteins on the cell surface or within luminal compartments of the secretory machinery, O-GlcNAc modifies myriad nucleocytoplasmic proteins. GlcNAcylated proteins are involved in transcription, ubiquitination, cell cycle, and stress responses. GlcNAcylation is similar to protein phosphorylation in terms of stoichiometry, localization and cycling. To date, only two enzymes are known to regulate GlcNAcylation in mammals: O-GlcNAc transferase (OGT), which catalyzes the addition of O-GlcNAc, and β- N-acetylglucosaminidase (O-GlcNAcase), a neutral hexosaminidase responsible for O-GlcNAc removal. OGT and O-GlcNAcase are regulated by RNA splicing, by nutrients, and by post-translational modifications. Their specificities are controlled by many transiently associated targeting subunits. As methods for detecting O-GlcNAc have improved our understanding of O-GlcNAc's functions has grown rapidly. In this review, the functions of GlcNAcylation in regulating cellular processes, its extensive crosstalk with protein phosphorylation, and regulation of OGT and O-GlcNAcase will be explored. GlcNAcylation rivals phosphorylation in terms of its abundance, protein distribution and its cycling on and off of proteins. GlcNAcylation has extensive crosstalk with phosphorylation to regulate signaling, transcription and the cytoskeleton in response to nutrients and stress. Abnormal crosstalk between GlcNAcylation and phosphorylation underlies dysregulation in diabetes, including glucose toxicity, and defective GlcNAcylation is involved in neurodegenerative disease and cancer and most recently in AIDS.